Penyuluhan Pemberian Kompres Dingin untuk Mengurangi Nyeri Pasien Fraktur - Khairunnisa Batubara; Romauli E.G. Siallagan (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
A fracture is a condition where the continuity of the bone is disrupted due to a hard impact, often causing significant pain in sufferers. Pain management does not only rely on pharmacological therapy but can also be combined with non-pharmacological therapies, one of which is through cold compresses using ice packs. This therapy is effective because it can reduce pain nerve conduction and reduce blood flow to the injured area, thereby suppressing pain. This activity aims to provide public education on the use of cold compresses as an alternative pain management in fracture cases. Before the activity began, vital signs were measured and a pain scale was assessed as a basis for evaluation. The education was carried out using leaflets by a team of lecturers and nursing students to 30 village community participants. Based on interviews, most participants had never received information about the benefits of cold compresses in pain management. Before the education, 23 participants were accustomed to managing pain with pain relievers, while the other 7 used other non-pharmacological methods such as hot compresses, deep breathing relaxation, and behavioral therapy. After participating in the activity, the community demonstrated an understanding that cold compresses using ice packs applied for 20 minutes when pain occurs can be a simple, inexpensive, and effective method for reducing pain caused by fractures. This activity involves village officials and the community as a collaborative effort to improve health literacy. It is hoped that the community will be able to implement cold compress therapy as a self-help option for managing fracture pain, thereby reducing reliance on analgesic medications.